Current use of guideline-based medical therapy in elderly patients admitted with acute heart failure with reduced ejection fraction and its impact on event-free survival. (15th May 2017) - Akita, Keitaro; Kohno, Takashi; Kohsaka, Shun; Shiraishi, Yasuyuki; Nagatomo, Yuji; Izumi, Yuki; Goda, Ayumi; Mizuno, Atsushi; Sawano, Mitsuaki; Inohara, Taku; Fukuda, Keiichi; Yoshikawa, Tsutomu; et al.
Abstract: Background: Acute heart failure (HF) is a frequently encountered cardiac condition. Its prevalence increases exponentially with age. In spite of this, elderly patients are underrepresented in clinical trials and the implementation of guideline-based medical therapy (GBMT) in them is not well established. We investigated the current use of GBMT and its effects on mortality and HF rehospitalization among elderly patients with acute HF with reduced ejection fraction (HFrEF) using data obtained from a contemporary multi-center registry. Methods and results: We analyzed data from 1, 441 consecutive acute HF patients registered in the West Tokyo Heart Failure (WET-HF) registry (mean age 73.2 ± 13.6 years). Reduced ejection fraction (< 45%) was noted in 803 patients (55.7%), of which 237 were aged ≥ 80 years (elderly group). The prescription rate of GBMT (use of renin-angiotensin system inhibitors and β-blockers at discharge) was significantly lower in the elderly than in the younger (aged < 80 years) group (46.8% vs. 66.9%, p < 0.001). Although GBMT at discharge was associated with reductions in HF readmission or the composite endpoint of cardiac death and HF readmission (HR 0.49, 95% CI 0.30–0.80; and HR 0.53, 95% CI 0.32–0.89, respectively) in the younger group, this association was not observed in the elderly group (HR 1.41, 95% CI 0.68–2.92; and HR 1.54, 95% CI 0.76–3.13, respectively) Conclusions: GBMT implementation in elderly patients with HFrEF was found to be suboptimal. However, the underuse of GBMT did not appear to be responsible for poorer outcomes in elderly HFrEF patients. Further research is required to establish an ideal therapeutic approach for this population. Clinical trial registration: URL:http://www.umin.ac.jp/icdr/index-j.html . Unique identifier: UMIN000001171. Highlights: Elderly HFrEF patients exhibited poorer prognoses and guideline-based medical therapy (GBMT) use rates than younger patients. The use of GBMT was associated with better clinical outcome among younger HFrEF patients, but not elderly patients. GBMT did not appear to be responsible for poorer long-term outcomes among elderly HFrEF patients.